Staphylococcus aureus ST398 Virulence Is Associated With Factors Carried on Prophage ϕSa3 - Kashif, Ayesha; McClure, Jo-Ann; Lakhundi, Sahreena; Pham, Michael; Chen, Sidong; Conly, John M.; Zhang, Kunyan (Frontiers in Microbiology, 2019)
An increasing number of severe infections caused by Staphylococcus aureus ST398 strains has been observed. However, it has not been elucidated whether all ST398 strains are equally virulent. We collected 13 strains from China and Canada to test in a Caenorhabditis elegans infection model and compared their whole genome sequences (WGS) to explore potential insights into their virulence. All isolates belonged to ST398-methicillin-susceptible S. aureus (MSSA) with variant spa types (t034, t571, t1451, t1250). Pulsed field gel electrophoresis (PFGE) and WGS analyses showed that the 13 isolates clustered into 3 genomic types (Types A-C). WGS and prophage phylogenetic analyses also revealed that the strains could be divided into 3 phage groups (Groups 1-3), which correlated with high-, moderate-, and low-nematocidal activities, with mean killing rates of 94%, 67%, and 40%, respectively. Group 1 carried fSa3-Group 1 (fSa3-G1), Group 2 carried fSa3-G2, and Group 3 lacked fSa3. Interestingly, strain GD1706 (that genetically clustered within Type C) and strain GD487 (within Type B) both carried fSa3-G1 like phages and killed 92% of the nematodes, similar to the Type A strains carrying fSa3-G1. This study demonstrated that different ST398 sub-lineages possess variable virulence capacities, depending on the presence or absence, as well as the structure of the prophage fSa3 that carries virulence factors.